PENGEMBANGAN KARTU KATA SEBAGAI MEDIA PEMBELAJARAN MENENTUKAN KATA SINONIM DAN ANTONIM BAGI SISWA KELAS V SEKOLAH DASAR - Tiamin; Ratno Abidin; Titik Kurniasari (PROCEEDING UMSURABAYA, 2024)
The aim of this research is to develop word card media that is appropriate and effective in improving mastery of determining synonyms and antonyms for fifth grade elementary school students. This research is development research, which consists of ten stages. The product produced is in the form of word card media to find synonym and antonym vocabulary, based on scores obtained from material experts and media experts, each with a score of 80 in the good category. The effectiveness of the product produced in improving vocabulary mastery of synonyms and antonyms in Indonesian is based on the results of hypothesis testing which obtained a significance (2-tailed) of 0. 034, smaller than 0. 05. Word card media is effective in improving the ability to find synonym and antonym vocabulary for elementary school students.